If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z(2z + 1) = 4z + 2 Reorder the terms: 3z(1 + 2z) = 4z + 2 (1 * 3z + 2z * 3z) = 4z + 2 (3z + 6z2) = 4z + 2 Reorder the terms: 3z + 6z2 = 2 + 4z Solving 3z + 6z2 = 2 + 4z Solving for variable 'z'. Reorder the terms: -2 + 3z + -4z + 6z2 = 2 + 4z + -2 + -4z Combine like terms: 3z + -4z = -1z -2 + -1z + 6z2 = 2 + 4z + -2 + -4z Reorder the terms: -2 + -1z + 6z2 = 2 + -2 + 4z + -4z Combine like terms: 2 + -2 = 0 -2 + -1z + 6z2 = 0 + 4z + -4z -2 + -1z + 6z2 = 4z + -4z Combine like terms: 4z + -4z = 0 -2 + -1z + 6z2 = 0 Factor a trinomial. (-1 + -2z)(2 + -3z) = 0Subproblem 1
Set the factor '(-1 + -2z)' equal to zero and attempt to solve: Simplifying -1 + -2z = 0 Solving -1 + -2z = 0 Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2z = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2z = 0 + 1 -2z = 0 + 1 Combine like terms: 0 + 1 = 1 -2z = 1 Divide each side by '-2'. z = -0.5 Simplifying z = -0.5Subproblem 2
Set the factor '(2 + -3z)' equal to zero and attempt to solve: Simplifying 2 + -3z = 0 Solving 2 + -3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3z = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3z = 0 + -2 -3z = 0 + -2 Combine like terms: 0 + -2 = -2 -3z = -2 Divide each side by '-3'. z = 0.6666666667 Simplifying z = 0.6666666667Solution
z = {-0.5, 0.6666666667}
| 2(x-12)=36 | | (p+9)(p+2)=-12 | | 7z+4=3 | | 3x^2-3x=-11x-4 | | -5x+8=9 | | 2x^2+1x=8x-5 | | 2x+7=7x+13 | | .11x+x=163 | | 1r^2-3r-70=0 | | m^2-4m-96=0 | | -3(8a-9)=5(9-5a) | | 3x+6x-8x= | | u^2=15u | | 2(3x+3)=5(x-5) | | 1/4(20+x)=30 | | 2(x-0.5)=4(x+4) | | p^2=10p+11 | | 1v^3=49v | | x(x+18)=-80 | | x-5=sqrt(-7x+43) | | y^2+10y=4x+3 | | 1d^2+29d+100=0 | | 5+0.5=2.67y+6 | | (2w+3)w=54*54 | | -4(5n-5)=2n | | x^2-17x=18 | | 2x/5+2/3(3x/5)+18=x | | 7(3n)/2=-6 | | -9x-1=-3 | | p(t)=1.8(1.4) | | Rl+rl=E | | 2+2w=8 |